O uso das tecnologias da informação e comunicação no ensino de geografia: aplicação da página protótipo Desenvolvimento Urbano do atlas municipal escolar de Ourinhos - Milena, Ana Paula Mateucci [UNESP] (2015)
Information and Communication Technologies (ICTs), seen by education, transformed the relationship of students with the school programs and brought new possibilities for teaching. With her was seen arise in Geography, digital and interactive maps that allow students new possibilities, with more interaction. And on the other, give the teacher tools to new teaching practices involving the use of technologies. Even allied to the incentive done by the National Curriculum Guidelines for the study of the place and making use of ICT develops the Municipal School Atlas of Ourinhos in digital form. To substantiate its proposal and understand how is student learning through this material, this research aimed to understand how the students to internalize concepts making use of animations, interactions, and other multimedia effects, construct knowledge; which will serve, above all, to guiding the drafting of the final version of the digital Atlas who yearns to contribute to the teaching of the place. Based on qualitative research, through ethnographic research and case study, an application prototype page was made Urban Development in the final years of elementary school, trying to analyze the feasibility and receipt of material. The results show that the material was well received among students and teachers, contributed to the study of concepts related to the Atlas, in addition to parallel content that it can work, thus demonstrating great potential for teaching